2014
DOI: 10.1039/c3cc48304e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine detection in the gas state and aqueous solution based on the Gabriel mechanism and its imaging in living cells

Abstract: A new probe based on the Gabriel mechanism was designed and first used for hydrazine detection with high selectivity against other amines in aqueous solution. Importantly, the probe could be used for gas-state discrimination of hydrazine with different concentrations. Additionally, probe could also be applied for the imaging of hydrazine in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(69 citation statements)
references
References 20 publications
2
67
0
Order By: Relevance
“…Moreover, CyJ could authenticate hydrazine vapor even with a concentration as low as 0.1%, which is extraordinary more sensitive than the current hydrazine probes. 32,35,52 These results confirmed that CyJ could not only test hydrazine in solution but also response to it upon its vapor state.…”
Section: Study On Reaction Mechanismsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, CyJ could authenticate hydrazine vapor even with a concentration as low as 0.1%, which is extraordinary more sensitive than the current hydrazine probes. 32,35,52 These results confirmed that CyJ could not only test hydrazine in solution but also response to it upon its vapor state.…”
Section: Study On Reaction Mechanismsupporting
confidence: 87%
“…However, to date, only a few papers are concerned with fluorescence methods for detection of N 2 H 4 . [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Many recognizing moiety of fluorescence sensors for N 2 H 4 have been developed, mainly including acetyl, [23][24][25][26] 4-bromo butyrate, [27][28][29] levulinate, 30,31 phthalimide, [32][33][34] aldehyde, 35 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Introductionmentioning
confidence: 99%
“…34 In our study, the designed nanohybrid material has been prepared from a surfactant free, facile and simple pathway where 2-propanol has been introduced for the first time as a potential reducing agent for GO, Au 3+ and Pd 2+ for the scalable synthesis of Au@Pd/rGO nanocomposites (GAP). 38,39 So this is highly recommended to develop a economically suitable sensing platform for N 2 H 4 . N 2 H 4 has been widely used in numerous fields such as aerospace, industries, military, pesticides, photography chemicals and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…This strategies involved in Gabriel synthesis has been successfully adapted for the development of fluorescent hydrazine probes, typically by incorporating phthalimide into amine‐containing fluorophores (Figure ). The first two phthalimide‐based fluorescent hydrazine probes ( 49 and 50 ) were reported simultaneously by Lin, Cui and their co‐workers by using 4‐aminonaphthalimide as the fluorescent reporters (Figure ) . In a mixture of PBS buffer (10 mM, pH = 7.2) and ethanol (1:9, v / v ), probe 49 exhibits a UV–vis absorption band and a fluorescence emission band at 344 and 467 nm, respectively.…”
Section: Probes Based On Phthalimide Moietymentioning
confidence: 99%